THE IMPACT OF RISK-BASED CAPITAL, PREMIUM INCOME, AND ASSET GROWTH ON FINANCIAL PERFORMANCE: THE MODERATING ROLE OF GOOD CORPORATE GOVERNANCE - Fikry Agustian; Andry Priharta (Taksasila Edukasi Insani, 2026)
This study examines the effects of Risk-Based Capital (RBC), premium growth, and asset growth on the financial performance of insurance companies, with Good Corporate Governance (GCG) as a moderating variable. Financial performance is proxied by Return on Assets (ROA). The study employs panel data from insurance companies listed on the Indonesia Stock Exchange during the 2020–2024 period and applies Moderated Regression Analysis (MRA) using EViews 12. The empirical results indicate that RBC has a significant negative effect on ROA, suggesting that excessive capital reserves may lead to inefficiencies in capital utilization. Premium growth is also found to have a significant negative impact on financial performance, implying that higher premiums are not necessarily accompanied by improved profitability due to increased claims and operational costs. Asset growth shows no significant effect on ROA, indicating that asset expansion alone does not guarantee better financial performance. Furthermore, GCG positively moderates the relationship between RBC and financial performance, mitigating the negative impact of high RBC levels. However, GCG does not significantly moderate the effects of premium growth and asset growth on ROA. These findings highlight the importance of effective corporate governance in optimizing capital management and improving financial performance in insurance companies.Keywords: Risk-Based Capital; Premium Growth; Asset Growth; Good Corporate Governance; Financial Performance